The wealth of information from transient guest profiles - Binder, Tomas; Chmelik, Christian; Heinke, Lars; Hibbe, Florian; Kärger, Jörg; Titze, Tobias; Tzoulaki, Despina (Diffusion Fundamentals, 2009)
The application of interference microscopy (IFM) and infrared microscopy (IRM) to monitor the evolution of the concentration of guest molecules in nanoporous host materials opens a new field of diffusion research in condensed matter. It combines the methodical virtues of the profiling methods of solid-state diffusion studies with the benefit of the mobility enhancement in fluids. We are going to illustrate the rich options of diffusion studies provided by this novel experimental approach.